Production and characteristics of a novel chicken egg yolk antibody (IgY) against periodontitis-associated pathogens. Issue 1 (1st January 2020) - Li, Xiangguang; He, Pan; Yu, Linjin; He, Qiyi; Jia, Chenggang; Yang, Huiyi; Lu, Minglei; Wei, Xiuting; Zhao, Suqing
ABSTRACT: Periodontitis is a bacterial biofilm-induced oral disease, mostly caused by Aggregatibacter actinomycetemcomitans ( A. actinomycetemcomitans ) and Porphyromonas gingivalis ( P. gingivalis ). Oral administration of chicken egg yolk antibody (IgY) is a promising nutritional strategy to control pathogen infections. The objective of this study was to produce an A. actinomycetemcomitans - and P. gingivalis -specific IgY and evaluate its effects on bacterial agglutination and biofilm formation. Thirty laying hens were immunized with a complex of lysate containing typical molecular weights of membrane proteins of A. actinomycetemcomitans and P. gingivalis . IgY was isolated by polyethylene glycol 6000 and ammonium sulfate and purified by dialysis. The results of enzyme-linked immunosorbent assay showed that the obtained IgY were specific to both A. actinomycetemcomitans and P. gingivalis . In addition, immunoelectron microscopy scanning and crystal violet staining showed that the IgY could bind to cell wall of the pathogens and efficiently accelerate agglutination and inhibit biofilm formation. Furthermore, the activity of the IgY remained stable at different temperature, pH, and storage period. This is the first report that a novel two-in-one IgY was produced to modulate the agglutination and biofilm formation of A. actinomycetemcomitans and P. gingivalis, suggesting the potential of IgY to control periodontitis caused by oral pathogens.